Numerical Heat Transfer and Fluid Flow Select Proceedings of NHTFF 2018 - Srinivasacharya, D.; Reddy, K. Srinivas (Lecture Notes in Mechanical Engineering, 2019)
This book comprises selected papers from the International Conference on Numerical Heat Transfer and Fluid Flow (NHTFF 2018), and presents the latest developments in computational methods in heat and mass transfer. It also discusses numerical methods such as finite element, finite difference, and finite volume applied to fluid flow problems. Providing a good balance between computational methods and analytical results applied to a wide variety of problems in heat transfer, transport and fluid mechanics, the book is a valuable resource for students and researchers working in the field of heat transfer and fluid dynamics.